Functional multigenic variations associated with hodgkin lymphoma. (3rd July 2021) - Osman, Yasser; Elsharkawy, Tarek; Hashim, Tariq Mohammad; Alratroot, Jumana Abdulwahab; Alsuwat, Hind Saleh; Otaibi, Waad Mohammed Al; Hegazi, Fatma Mohammed; AbdulAzeez, Sayed; Borgio, J. Francis
Abstract: Introduction: The current study aimed to describe genotypes associated with Hodgkin lymphoma (HL) in a cohort of Saudi and non‐Saudi patients and discuss their possible susceptibility to HL. Methods: We studied clinical, histopathological, and laboratory findings of HL patients admitted over 12 years duration, at King Fahd University Hospital, KSA. The genomic DNAs of HL patients (n = 61) and normal control subjects (n = 36) were extracted, and genotyping was performed using the Illumina human exome bead chip. Set of HL patients and set of normal controls were included in this study. Results: A total of 35 DNA variants were found to be highly significant with the P ‐value <9.90 × 10 −11 among 243 345 exonic biomarkers and obeying the Hardy‐Weinberg equilibrium. Nine, MEGF11‐rs150945752 ( P ‐value 1.20 × 10 −12 ), CACNA1I‐ s58055559 ( P ‐value 1.93 × 10 −12 ), DECR2‐ rs146760080 ( P ‐value 2.19 × 10 −12 ), STAB1‐ rs143894786 ( P ‐value 2.45 × 10 −12 ), ZNF526‐ rs144433879 ( P ‐value 2.76 × 10 −12 ), CPLANE1‐ rs200612080 ( P ‐value 3.77 × 10 −12 ), DLK1‐ rs1058009 ( P ‐value 5.95 × 10 −12 ), RTN4RL2‐ rs61745214 ( P ‐value 7.71 × 10 −12 ), and PGRMC1‐ rs145582672 ( P ‐value 8.56 × 10 −12 ), exonic variants on chromosomes 15, 22, and 16 were highly associated with HL cases. The highly significant haplotypes at chromosome 3: rs143894786G; rs149982219G with P ‐value = 3.43 × 10 −14 was found to be the risk haplotype for the HL patients. The opposite alleles at chromosome 3: rs143894786A; rs149982219G is protective with P ‐value = 2.46 × 10 −12 . Maximum number of SNPs at the chromosome 19: rs144433879C; rs181265966G; rs201144421C; rs145591797G; rs200560875G; rs77270337G (risk P ‐value = 2.24 × 10 −12 ) and its opposite allele rs144433879A; rs181265966A; rs201144421T; rs145591797A; rs200560875A; rs77270337A (protective P ‐value = 2.60 × 10 −9 ) were found to be associated haplotype with the HL and controls, respectively, in Saudi population. Conclusion: Our study concludes that the HL is genetically heterogeneous with multigene causation.